Anticerebral oedema therapy in Reye's syndrome. Issue 12 (December 1975) - Lovejoy, F H; Bresnan, M J; Lombroso, C T; Smith, A L
Abstract : Sixteen patients with Reye's syndrome were seen over a 3-year period and treated with conservative management with an overall mortality of 31%. 6 of the 16 had illness limited to stages II and III. Intensive therapy of suspected cerebral oedema, with careful monitoring of serum osmolarity, was associated with survival in 5 of 10 patients with stage IV disease. The risks of lumbar puncture in the presence of cerebral oedema (stages III-IV) are emphasized. A change in clinical status (usually a reversal to a less severe stage and an improved electroencephalogram) was seen within hours of starting anticerebral oedema therapy. Neurological sequelae (memory deficit, hemiparesis, hemiballismic movements, and delayed motor milestones) that were present in stage IV survivors at discharge were absent 12 months after discharge. Conservative supportive management emphasizing treatment of presumed cerebral oedema in severe cases of Reye's syndrome has a mortality comparable to that occurring in exchange transfusion or peritoneal dialysis. This form of therapy should be included in controlled trials to determine which form of therapy is optimal.